2004
DOI: 10.1111/j.1399-0004.2004.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the impact of messages about genes and race on lay attitudes

Abstract: The effect of messages about genetics on lay audiences was assessed through an experimental study that exposed participants (n = 96) to a Public Service Announcement about race, genes, and heart disease. Participants who received a message that specified either 'Whites' or 'Blacks' as the subject of the message demonstrated elevated levels of racism, genetic basis for racism, and one dimension of genetic discrimination as compared to those receiving a version of the message with no race specification or in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 21 publications
7
67
0
Order By: Relevance
“…1,2 However, others express concern about the lack of clarity and consistency around the assignment of racial categories, along with fear of increased bias, discrimination, and reinforced stereotypes that may shift focus away from important social determinants of health. [3][4][5][6][7][8] One study, in fact, demonstrated that lay audiences exposed to messages about genetics that are linked to either 'Whites' or 'Blacks' were more likely to endorse higher levels of racism, beliefs about a genetic basis for racism, and genetic discrimination. 4 To date, the bulk of this debate is in the academic arena and focuses on genetic research in more general terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, others express concern about the lack of clarity and consistency around the assignment of racial categories, along with fear of increased bias, discrimination, and reinforced stereotypes that may shift focus away from important social determinants of health. [3][4][5][6][7][8] One study, in fact, demonstrated that lay audiences exposed to messages about genetics that are linked to either 'Whites' or 'Blacks' were more likely to endorse higher levels of racism, beliefs about a genetic basis for racism, and genetic discrimination. 4 To date, the bulk of this debate is in the academic arena and focuses on genetic research in more general terms.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] One study, in fact, demonstrated that lay audiences exposed to messages about genetics that are linked to either 'Whites' or 'Blacks' were more likely to endorse higher levels of racism, beliefs about a genetic basis for racism, and genetic discrimination. 4 To date, the bulk of this debate is in the academic arena and focuses on genetic research in more general terms. Sterling et al recently performed a systematic review of studies examining public opinions on GVR and found only one study that prompted discussion about research specifically on the relationships of race, genes, and health.…”
Section: Introductionmentioning
confidence: 99%
“…In past research lay health consumers have expressed concerns that the cost and availability of new medications may result in widening health inequalities [3] and that genetic testing might lead to breaches of confidentiality, misuse of positive test results, and discrimination by insurers [4]. In addition marketing messages linking race, genes, and heart disease that specified blacks or whites as the subject of the message led to higher levels of racist attitudes such as belief in a genetic basis for racism [5]. …”
Section: Introductionmentioning
confidence: 99%
“…This may change how the term is perceived by the reader (especially when mixed with readers' interpretations). 4,24 Although many specialized scientific terms are explained and simplified in the media, population terminology is not treated as specialized, and, as such, readers are able to bring their own definitions to the words, which can vary widely according to geographical location, culture, personal history, and education. 20 -22 Our study has clear limitations, the sample size is relatively small (a result of seeking complete sets that include peerreviewed article, press release, and media report).…”
Section: Discussionmentioning
confidence: 99%